대한민국 건국과 기독교인의 음악활동 - 정경은(CHUNG Kyeong-Eun) (Changsin nondan, 2013)
한국의 양악(洋樂)은 식민지 상황, 좌우익의 대립, 동족간의 전쟁이라는 특수한 상황에서 전개 되었다. 이 과정에서 교회와 기독교 학교 그리고 기독교인부모를 통해 양악을 받아들이고 성장한 기독교 음악인들은 의미 있는 활동을 보여주었다. 해방 후 관현악단, 합창단, 음대, 군악대, 음악단체의 활동가들 대부분은 기독교 학교와 교회에서 양악을 처음 접한 기독교인들이었다. 1945년 일본으로부터의 해방과 함께 음악인들은 자유롭게 자신이 원하는 음악활동을 시작하였고 가장 먼저 착수하였던 것은 교향악단 활동과 새로운 교육기관의 창립이었다. 해방 후 기독교 음악가들은 건국과 관계된 음악과 노래를 짓고 불렀으며다양한 음악활동을 통하여 현대 음악의 기초를 닦았다. 후진 양성에도 힘을 써학교를 설립하였으며, 초·중등 음악교재의 발간에도 많은 관심을 보임으로 현대 음악교육의 기틀을 세웠다. 기독교인 음악가들은 해방과 전쟁의 혼란기에 대한민국의 건국에 힘을 썼으며, 이들의 음악으로 인해 민중은 위로를 받았다. 기독교 음악인들의 활동은 시간과 공간을 초월하여 전 문화계에서 발견되고 있으므로, 굳이 기독교 음악인의활동이라고 구분하지 않아도, 해방 후에서 전쟁기간 동안 모든 음악활동에 이들이 참여하였기 때문에 현대 음악사와 다른 양상을 보이지 않는다. 이 시기에 종교음악과 일반음악이 크게 구분되지 않았다는 것인데, 이는 앞으로 종교음악과기독교인 음악가들의 활동에 시사하는 바가 크다고 하겠다. Western music in Korea developed under an unusual circumstance: years of colonization,a conflict between the left and the right, and a fratricidal war. Christian musicians, who were raised under the influence of church, Christian schooling, and Christian parents, made a significant contribution over this process. Most musicians who were active in orchestras,choirs, colleges of music, military bands, and musical organizations after the national independence were Christians who had been exposed to Western music through Christian schools or churches. Now that the Japanese colonial government was gone, these musicians were free to pursue their musical interests and went on to form symphony orchestras and found new educational institutes. They also wrote and performed songs related to the establishment of the Republic of Korea and laid the groundwork for modern music through various musical activities. Last but not least, they also educated the younger generation by publishing music textbooks for elementary and middle school and established new schools, thereby establishing the basis for modern music education. In such ways, Christian musicians put forth a vast effort for national foundation amidst the chaos after the liberation and during the war, and the people took comfort from their music. Because Christian musicians participated in most musical activities after the independence,there is not much difference between an account of these musicians and an account of Korean modern music in general. Religious music during this period, in other words, was rather undifferentiated from music in general, a fact that provides implications for religious music and careers of Christian musicians in the future. KCI Citation Count: 3